A MINERALOGICAL STUDY OF SOME MYCENAEAN SEALS EMPLOYING MOBILE RAMAN MICROSCOPY - Economou, G.; Konstantinidi-Syvridi, E.; Kougemitrou, I.; Perraki, M.; Smith, D.C. (Bulletin of the Geological Society of Greece, 2010)
The National Archaeological Museum in Athens is the largest archaeological museum in Greece, and one of the most important museums in the world, devoted to Ancient Greek art and history. Among other exhibits, it owns a large collection of gemstones some of which were used during prehistoric times (Mycenaean period) as seals. Their shape varies from round to oval, flattish or cylindrical, and they are delicately engraved as intaglios with a variety of depictions (lions, bulls, man, etc). They show a wide range of colours from reddish, brown, to purplish and blue. The six sealstones described here come from the Chamber Tombs of Mycenae (15th-14th cent. BC). Museum exhibit labels recognize them as varieties of quartz such as jasper (NAM 3138), sardonyx (NAM 2316 & 2865), agate (NAM 4928), amazonite (NAM 2863) and gold-mounted carnelian (NAM 6489). Raman Spectroscopic analysis has been carried out with a new MRM (Mobile Raman Microscope) using a Kaiser Holoprobe with a NIR 785nm laser. The Raman spectra acquired from 1s-60s measurements confirmed that, in all six sealstones, quartz was the major mineral species clearly identified by its characteristic peaks. The second most important phase was moganite, a little-known polymorph of quartz. The amber-coloured sealstone (NAM 6489) was confirmed as carnelian, whereas the blue-green amazonite-coloured sealstone (NAM 2863) was not detected as amazonite. Small amounts of haematite were detected in the NAM 2865 & NAM 3138.